Is Students’ Satisfaction in Electrical Engineering Courses Influenced by Gender? - Leão, Celina P. (2018)
Electrical/Electronic Engineering courses are often regarded as male courses. In this paper it is presented a study conducted in two Portuguese and two Brazilian high education institutions (six courses) where the goal was to analyze if gender affects students’ perceptions and satisfaction regarding Electrical/Electronic Engineering courses. The analysis was based on 654 questionnaires rating 44 items (among the six groups: Teacher Involvement Perception, Student Interest, Student-Teacher interaction, Course organization and functioning, Infrastructures, and Overall satisfaction). The investigation was performed by year, from the first to the third year (1st cycle) and considering the six programs. Based on students’ perceptions, some items showed differences that were significant, namely the ones regarding how teachers and students interact and how teachers challenge students.